PROSES BISNIS SISTEM PENERIMAAN NEGARA (MPN G3) TERHADAP PENERIMAAN DI MASA PANDEMI - Anastasya Utami; Muhammad Rafi Bakri (Jurnal Acitya Ardana, 2022)
The Government Receipt System is a collaborative system carried out by billers (DGT, DJA, and DJBC), the State Treasury Service Office (KPPN) for Revenues, the Directorate of Treasury Information & Technology Systems, and the Directorate of State Treasury Management which aims to collect state revenues in an integrated system. The purpose of this study was to determine the business process analysis of the Third Generation of Government Receipt System (MPN G-3) on receipts during the pandemic at KPP Pratama Aceh Besar. KPP Pratama Aceh Besar is one of the billers that utilizes MPN G-3 to collect state revenues in taxation. The data collection methods used are library research, interviews, and online observations. The data used were obtained from sources and literature. The results of this study indicate that MPN G-3 is a brilliant innovation because it can increase the percentage of realized tax revenues, explore the potential of each function related to MPN, and explore the potential of sections related to these functions to collect state revenues in the taxation sector to achieve the target set that already determined.